2023
DOI: 10.1021/acscatal.3c03332
|View full text |Cite
|
Sign up to set email alerts
|

Single Cobalt Atoms Induced Molecular O2 Activation for Enhanced Photocatalytic Biomass Upgrading on ZnIn2S4 Nanosheets

Xinying Tan,
Shenghe Si,
Difei Xiao
et al.

Abstract: Photocatalytic selective biomass aerobic oxidation to high-value products is promising for meeting carbon-neutral demand; however, great challenges remain in the lack of appropriate active sites for molecular O 2 activation and understanding their role at the atomic scale to reveal the underlying mechanism. Herein, we report that a rational decoration of ultralow-amount (0.08 wt %) Co single atoms on ZnIn 2 S 4 nanosheets (Co 1 /ZIS) enables both high activity and selectivity for photocatalytic 5-hydroxymethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…It should be noted that using CN panels in continuous-flow conditions, we achieved high HMF conversion rate (1185 μmol h –1 g –1 ), which is among the state-of-the-art heterogeneous photocatalysts (Figure c and Table S5). Postoperational characterization studies emphasize the structural and chemical stability of the panel after a continuous operation for 24 h (Figures S28 and S29). This stability and the high HMF conversion in pure water motivate the adaptation of continuous-flow photochemistry to oxidation reactions of more challenging biomass substrates (e.g., lignin, cellulose, and glycerol).…”
Section: Results and Discussionmentioning
confidence: 99%
“…It should be noted that using CN panels in continuous-flow conditions, we achieved high HMF conversion rate (1185 μmol h –1 g –1 ), which is among the state-of-the-art heterogeneous photocatalysts (Figure c and Table S5). Postoperational characterization studies emphasize the structural and chemical stability of the panel after a continuous operation for 24 h (Figures S28 and S29). This stability and the high HMF conversion in pure water motivate the adaptation of continuous-flow photochemistry to oxidation reactions of more challenging biomass substrates (e.g., lignin, cellulose, and glycerol).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Various modification methods, such as heterostructure design, defect engineering, co-catalyst loading, and element doping, have been employed for fine-tuning of the coordination environment and electron distribution of active sites in ZIS. 26–29 Previous studies have demonstrated that the d orbital configuration significantly impacts the electronic properties of transition metal cations on the catalyst surface, as well as their interaction with reactants. 30–33 Norskov et al introduced the d-band center theory, which has been proven to be an indicator of the binding strength of key intermediates in catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%